Nanyang : Essays on Heritage - Wang, Gungwu (Project Muse, 2018)
This volume is a book of reflections and encounters about the region that the Chinese knew as Nanyang. The essays in it look back at the years of uncertainty after the end of World War II and explore the period largely through images of mixed heritages in Malaysia and Singapore. They also look at the trends towards social and political divisiveness following the years of decolonization in Southeast Asia. Never far in the background is the struggle to build new nations during four decades of an ideological Cold War and the Chinese determination to move from near-collapse in the 1940s and out of the traumatic changes of the Maoist revolution to become the powerhouse that it now is.